Ang Tatay kong nanay - Nadres, Orlando; Batac, Jose.; Lahad, Lutgardo; Dolphy; Muhlach, Nino.; Salvador, Philip; Delgado, Marissa; Villanueva, Lorli; Brocka, Lino.; Yu, Jesus B.; Salvador, Augusto; Lotus Films; et al. ([Metro Manila Lotus Films], 1976)
Dolphy stars with Nino Muhlach in a drama about a gay who brings up a young boy as his own son.
Story and screenplay, Orlando Nadres ; cinematography, Jose Batac, Jr. ; music, Lutgardo Lahad ; film editor, Augusto Salvador ; executive producer, Jesus B. Yu ; Direction, Lino Brocka.
Dolphy, Nino Muhlach, Philip Salvador, Marissa Delgado, Lorli Villanueva, Soxy Topacio, Orlando Nadres.
VHS, Hi-Fi.
Keywords: Beauty operators -- Philippines -- Drama; Gay men -- Philippines -- Drama; Parenting -- Philippines -- Drama; Gay men in motion pictures; Feature films